Pengaruh Profesionalisme Kerja dan Sarana Prasarana terhadap Pegawai di Kantor Kesyahbandaran dan Otoritas Pelabuhan Kelas III Sunda Kelapa - Wibowo, Wiyono; Madiistriyatno, Harries; Taufik, Kemal (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
To be able to know and analyze the influence of Work Professionalism on Employee Performance. To be able to know and analyze the influence of Facilities and Infrastructure on Employee Performance. To be able to know and analyze simultaneously or together how much influence Work Professionalism and Facilities and Infrastructure have on Employee Performance at the Harbormaster and Port Authority Office Class III Sunda Kelapa. The population in the study at the Harbormaster and Port Authority Office Class III Sunda Kelapa there were 67 employees as the population. So the sampling technique in this study the author used the Total Sampling technique or overall there were 67 population people who were sampled 100% or 67 employees. Positive influence of Work Professionalism on Employee Performance obtained a partial value of 0.928 meaning there is a very strong influence or influence with a determination coefficient of 86.1%. This is proven by the hypothesis test of the variable of Work Professionalism on Employee Performance obtained a value of to = 6.869 > t0.05 (65) = 1.670, then Ho is rejected and Ha is accepted, meaning there is a very significant effect. Based on the calculation results, there is a positive effect of Facilities and Infrastructure on Employee Performance, a partial value of 0.863 is obtained, meaning there is a very strong effect or its effect with a coefficient of determination of 74.5%. This is proven by the hypothesis test of the variable of Facilities and Infrastructure on Employee Performance, obtaining a value of to = 3.474 > t0.05 (65) = 1.670, then Ho is rejected and Ha is accepted, meaning there is a significant effect. Simultaneously the positive influence of the variables of Work Professionalism and Facilities and Infrastructure on the variable of Employee Performance with a simultaneous correlation value or Model Summary produces an R value of 0.916 and while the R Square value is 0.839 or 83.9%, this can be stated that the results of the analysis together the variables of Work Professionalism and Facilities and Infrastructure on the variable of Employee Performance have a very strong influence. Proven through the results of the F test (ANOVA) or F count obtained a value of 18.255 which is greater than F table (66) of 2.750 with a significant level of 0.000 because 0.000 <0.05, then it can be said that the variables of Work Professionalism and Facilities and Infrastructure together or simultaneously on Employee Performance have a significant influence.